Correlation between natural exposure and artificial ageing test for typical marine coating systems. Issue 36 (3rd June 2016) - Zhang, Hanlu; Dun, Yuchao; Tang, Yuming; Zuo, Yu; Zhao, Xuhui
ABSTRACT: Natural exposure test at Sanya and artificial ageing test were carried out for four kinds of typical marine coating system, respectively. The gloss, surface morphology, coating impedance, and infrared spectra of the coatings were measured with methods of SEM, EIS, and FT‐IR. The correlation between results from artificial ageing test and natural exposure test was discussed. The fluorocarbon paint showed longer ability to remain high gloss than polyurethane paint. The xenon lamp ageing test and natural exposure test led to similar changes in surface morphology of the coatings. For polyurethane paint under both tests, with extended testing time micropores and cracks occurred gradually on the surface, meantime the coating gloss decreased. The increase of the defect area corresponded well to the decrease of the coating gloss, suggesting that the degradation extent of the coating surface could be reflected by the gloss measurement. The rank correlation study showed that the results by 60 d, 150 d, 300 d, 360 d, and 450 d natural exposure, respectively, were very close to those by 228 h, 443 h, 841 h, 1958 h, and 4013 h artificial ageing test. Hence, the artificial xenon lamp ageing test may be used to simulate natural exposure test at Sanya. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43893. Abstract :